The Effect of Trait and Factor Theory-Based Career Counseling Services on Career Decision Making at As Salafi Balun Vocational School - Saifuddin, Ahmad; Maghfiroh, Nasruliyah Hikmatul; Sukmawati, Bhennita (Journal of English Language and Education, 2025)
This study investigates the effect of Trait and Factor theory-based career counseling services on career decision-making among twelfth-grade students at As Salafi Balun Vocational School. The research addresses the prevalent confusion and uncertainty in career selection due to limited self-understanding and inadequate guidance. Employing a quantitative pre-experimental design with a one-group pretest–posttest model, all 17 students in the target population participated. Data were collected using a validated career decision-making questionnaire and analyzed with descriptive statistics, paired sample t-tests, Wilcoxon Signed-Rank tests, and effect size calculations. The results show a significant improvement in students’ career decision-making abilities, with posttest scores markedly higher than pretest scores and a very large effect size. The findings confirm that structured Trait and Factor-based counseling enhances career maturity and reduces indecision. In conclusion, the intervention is effective in fostering informed career choices, though future studies should consider larger samples and longer follow-up periods.